Subacute toxicity study of an aqueous extract of dried leaves of Gymnosporia spinosa on albino rats - Kubavat, Amita R.; Rajguru, Hetal D.; Malek, Shahenaz M. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Leaves of Gymnosporia spinosa have been used by people for treatment of jaundice. Traditional herbal drugs are popular all over the world and it is presumed that herbal medicines have lesser or no side effects. This generalized belief and no information available regarding toxicity study of G. spinosa with search from limited available information prompted us to carry out work on subacute toxicity study of aqueous extract of dried leaves of G. spinosa. Methods: Subacute toxicity study was carried out using aqueous extract of G. spinosa leaves. 30 rats of either sex were randomly divided in to 4 groups. First group received distilled water (control). Second, third and fourth groups received single daily dose of drug orally as 40, 120 and 240 mg/100 g of body weight respectively for 3 weeks. Animals were observed for various parameters. After 21 days blood was collected for blood counts and biochemical parameters. Liver, lungs and kidney were subjected to histo-pathological studies. Results: Throughout study there was no mortality in any group. Degenerative changes in the liver. Other organ does not show any changes. Analysis of biochemical data showed serum glutamic pyruvic transaminase and s. alkaline phosphatase levels were decreased. Serum bilirubine, blood urea and serum creatinine level were increased significantly. Conclusions: The data showed that there was hepato-renal toxicity at higher dose level which is about 100x human therapeutic dose.